Improving Students’ Pronunciation Through Rap Song in Advanced Class at Smaru Gondanglegi - Musolli, Anam (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Mastering English pronunciation remains one of the greatest challenges for EFL learners, particularly in mastering stress, rhythm, and intonation. Traditional drilling methods often feel monotonous and ineffective, leading to disengagement and slow progress. This study explores rap music as a transformative tool that blends rhythm, repetition, and phonetics to enhance pronunciation learning. Implementing a Classroom Action Research (CAR) approach, the study involved 15 advanced students at SMA Raudlatul Ulum Gondanglegi. The intervention combined rap music with phonetic symbols, providing a structured yet dynamic approach to pronunciation practice. Data were gathered through pre- and post-tests, classroom observations, and student feedback surveys. Results showed a remarkable improvement, with an average increase of 18% in post-test pronunciation scores. Moreover, students exhibited heightened confidence, engagement, and enthusiasm in speaking activities. These findings highlight rap music as a powerful and innovative alternative to traditional pronunciation instruction, offering a more immersive and motivating learning experience. Future research should examine its long-term effects and potential integration into broader language learning curricula.